Solar Roadway: Modular Approach for Renewable Energy: An Innovative Solution for Meeting India's Energy Demands (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The need of energy sources and new technology for electricity generation is increasing day by day, one such source can be solar energy, which is renewable source and is limitless. A major drawback of solar source is that it needs more space for electricity generation. As pavements are often exposed to a vast amount of solar radiation, it is possible to extract a portion of this energy through the implementation of solar roadways. Infrastructural growth of India and area availability for roadways is only reason to use road surface for electricity generation. A modular approach is adopted to elaborate and understand the theory of solar roadways. Surface area about 60-65 is covered by solar panels which are converting solar energy to electrical energy. This study concludes that this can be implemented in large scale as resulted in model.This is an energy saving approach to meet the energy demands of India.